Directors’ characteristics, Firm-specific factors, and Shariah-compliant status: A logit model analysis in Pakistan - Qazi Muhammad Haris; Dr. Amena Sibghatullah; Dr. Muhammad Azam; Muhammed Usman Khalid (Migration Letters, 2023)
The purpose of this study is to identify the major factors that are significantly influencing the Shariah-compliant status of the listed firms on the Pakistan Stock Exchange (PSX). This research examines the extent to which variations in directors’ characteristics and firm-specific factors affect the company’s status concerning Shariah compliance. A total of 80 listed companies on the Pakistan Stock Exchange were selected. The data were collected from the companies’ financial reports from 2013 to 2017 (N=400). The research models were tested using fixed and random effects logit analysis on STATA 15. The findings reveal that the director’s religion, Islamic financing, Islamic institutes’ shareholdings, payout ratio, and stock return significantly influence Shariah-compliant status in Pakistan. This study is the first to explore the directors’ characteristics and firm-specific factors that impact Shariah-compliant status to the best of our knowledge.